2016
DOI: 10.1371/journal.ppat.1005913
|View full text |Cite
|
Sign up to set email alerts
|

Tbet Deficiency Causes T Helper Cell Dependent Airways Eosinophilia and Mucus Hypersecretion in Response to Rhinovirus Infection

Abstract: Current understanding of adaptive immune, particularly T cell, responses to human rhinoviruses (RV) is limited. Memory T cells are thought to be of a primarily T helper 1 type, but both T helper 1 and T helper 2 memory cells have been described, and heightened T helper 2/ lessened T helper 1 responses have been associated with increased RV-induced asthma exacerbation severity. We examined the contribution of T helper 1 cells to RV-induced airways inflammation using mice deficient in the transcription factor T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…This is not surprising, as the NS1 protein of PR8 is known to antagonize type I IFN responses (39). Others have shown that RV induces expression of type I and type III IFNs in the respiratory tracts of infected mice (29,40,41). We further showed that RV/PR8-infected mice had increased IFN-␤ expression early in coinfection (day 2), which was not sufficient to reduce PR8 replication in the lungs at early time points (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…This is not surprising, as the NS1 protein of PR8 is known to antagonize type I IFN responses (39). Others have shown that RV induces expression of type I and type III IFNs in the respiratory tracts of infected mice (29,40,41). We further showed that RV/PR8-infected mice had increased IFN-␤ expression early in coinfection (day 2), which was not sufficient to reduce PR8 replication in the lungs at early time points (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…As a central regulator of type 1 immunity, T-bet has been implicated in infections by pathogenic bacteria and parasites affecting the lungs, skin, central nervous system and gut (reviewed by , wherein loss of function mostly resulted in greater pathogen burden. Nevertheless, a recent study found that the loss of T-bet did not result in marked defects in the ability to clear acute respiratory syncytial virus (RSV) infection despite reduced cellular and humoral antiviral responses, but instead led to increased allergic responses (Glanville et al, 2016). Beyond acute infections, T-bet is also involved in secondary antiviral defences through mediating the formation of memory B and T cells (Joshi et al, 2007;Marshall et al, 2011;Knox et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Its functions are hitherto known to be mediated through the expression of cytokines IFNc and IL-12, chemokines CCL3 and CCL4 as well as chemokine receptors such as CXCR3. Earlier studies demonstrated its requirement for control of Vaccina virus and herpesvirus infections (Matsui et al, 2005;Svensson et al, 2005;Rubtsova et al, 2013), while a recent study showed that loss of T-bet did not affect eventual viral clearance from rhinovirus infection, but is instead involved in suppression of viral-mediated allergic airway response (Glanville et al, 2016). As a result, T-bet is purportedly required for immune defence against many classes of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Tbet 2/2 mice developed a T H 2/ T H 17-polarized immune response to RV infection (5 3 10 6 TCID 50 ) with increased IL-13 and IL-17A production, deficient NK cell responses, and decreased neutralizing antibody development. 161 CD4 1 T cells contributed to increased airway eosinophil numbers and mucus production following RV infection in Tbet 2/2 mice. 161 Studies using TSLP receptor-deficient mice (TSLPR 2/2 ) demonstrated that RV-A1 infection interferes with tolerance to an inhaled allergen, via a mechanism requiring TSLP, IL-33, and activation of OX40L on lung dendritic cells.…”
Section: Technical Details and Main Findings From Mouse Rhinovirus Inmentioning
confidence: 91%
“…161 CD4 1 T cells contributed to increased airway eosinophil numbers and mucus production following RV infection in Tbet 2/2 mice. 161 Studies using TSLP receptor-deficient mice (TSLPR 2/2 ) demonstrated that RV-A1 infection interferes with tolerance to an inhaled allergen, via a mechanism requiring TSLP, IL-33, and activation of OX40L on lung dendritic cells. 162 After observing increased levels of the TNF super family member protein, Tnfsf10 (TRAIL or CD253) production over a time course of RV-A1 infection in mice, Girkin et al compared RV-A1 infection in Tnfsf10 2/2 mice to wild-type BALB/c mice and observed an almost complete ablation of inflammatory responses to RV-A1.…”
Section: Technical Details and Main Findings From Mouse Rhinovirus Inmentioning
confidence: 91%